2020
DOI: 10.1159/000508103
|View full text |Cite
|
Sign up to set email alerts
|

The Cut-off Limits of Growth Hormone Response to the Insulin Tolerance Test Related to Body Mass Index for the Diagnosis of Adult Growth Hormone Deficiency

Abstract: Introduction: The diagnosis of growth hormone deficiency (GHD) in adults is based on a reduced GH response to provocative tests, such as the insulin tolerance test (ITT) and the GH-releasing hormone (GHRH) + arginine (ARG) test. However, the cut-off limits of peak GH response in lean subjects are not reliable in obese patients; this is noteworthy since adult GHD is often associated with obesity. To date, there are no ITT cut-offs related to body mass index (BMI). Objective: We aimed to evaluate the diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…The GH response to GHRH + ARG test was defined as normal when GH > 11.0 mg/l for lean subjects, when GH > 8.0 mg/l for overweight subjects and when GH > 4.0 mg/l for obese subjects (1,21). The GH response to ITT was defined as normal when GH > 3.5 mg/l for lean subjects and when GH > 1.3 mg/l for overweight or obese subjects, in agreement with a recent paper that has identified these as the best BMI-related GH cutoffs for the diagnosis of GHD at ITT (28). Patients with a concordantly normal response to both tests were considered as having a normal function of the somatotroph axis.…”
Section: Data Collectionsupporting
confidence: 79%
“…The GH response to GHRH + ARG test was defined as normal when GH > 11.0 mg/l for lean subjects, when GH > 8.0 mg/l for overweight subjects and when GH > 4.0 mg/l for obese subjects (1,21). The GH response to ITT was defined as normal when GH > 3.5 mg/l for lean subjects and when GH > 1.3 mg/l for overweight or obese subjects, in agreement with a recent paper that has identified these as the best BMI-related GH cutoffs for the diagnosis of GHD at ITT (28). Patients with a concordantly normal response to both tests were considered as having a normal function of the somatotroph axis.…”
Section: Data Collectionsupporting
confidence: 79%
“…The GHRH + ARG test has been shown to distinguish adult patients with GHD from normal subjects with a sensitivity comparable to the ITT, considering appropriate BMI-related cutoffs [69, 75]. Indeed, the GH response to GHRH + ARG is negatively associated with BMI (Table 1), as also recently demonstrated for the ITT [76]. Thus, the GHRH + ARG test could be the first choice in the elderly for its safety profile and the lack of significant contraindications, except for chronic renal failure [77].…”
Section: Gh Deficiencymentioning
confidence: 75%
“…A BMI-adjusted GH response to GHRH-arginine (BMI <25: peak <11 μ g/L, BMI 25–30: peak <8 μ g/L, BMI >30: <4 μ g/L) is a strong indicator of GHD, although a normal response does not exclude GHD. To examine the well-known negative association between GH response to stimulation tests and BMI, Gasco and colleagues studied 106 patients who underwent GHRH + arginine stimulation as well as an ITT, enabling investigators to establish BMI cut-offs for diagnosing adult GHD [ 23 ]. The ITT is especially preferred when damage to the hypothalamus is suspected.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have compared the ITT with alternative tests including morning cortisol [ 24 , 25 ], ACTH stimulation test [ 26 , 27 ], GHRH + arginine [ 28 ], and glucagon [ 29 ]. A recent study demonstrated that with appropriate BMI cut-off limits, the ITT is a reliable test to diagnose adult GHD [ 23 ]. However, the ITT (with adequate hypoglycaemia) is superior to other endocrine tests of combined GH responsivity [ 4 ] and HPA axis integrity.…”
Section: Discussionmentioning
confidence: 99%